Development of Augmented Reality Learning Media with Ethnomathematics to Improve Critical Thinking Skills - LL. Gede Damar Wulan; Sudi Prayitno; Dwi Novitasari (Mandalika Mathematics and Educations Journal, 2026)
This study aims to develop an augmented reality learning media using an ethnomathematical approach on curved-sided geometric shapes that is valid, practical, and effective in improving students' critical thinking skills. This research and development (R&D) study adapted the 4D model. The sample consisted of 27 ninth-grade students from a junior high school in West Lombok. The augmented reality media was developed using Assemblr Edu in the form of interactive 3D worlds featuring Sasak cultural objects. During the development stage, two trials were conducted to obtain data on practicality and effectiveness. Research instruments included expert validation questionnaires (media and content), practicality questionnaires for teachers and students, and pretest and posttest questions on critical thinking skills. Data were analyzed using Aiken's V index for validity, percentages for practicality, and normalized gain (g) for effectiveness. The results showed that the developed augmented reality learning media was (1) valid, with an average Aiken's index score of 0.92; (2) practical, with an average practicality percentage of 92%; and (3) effective in improving students' critical thinking skills, with an average normalized gain (g) of 76%. Thus, the developed augmented reality learning media with an ethnomathematical approach is effective in enhancing students' critical thinking skills